Faith & reason: a synthesis in Pakistani society - Naveed Yazdani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
The basic objectives of this paper are to build a general level of understanding towards the need for synthesizing and harmonizing religious, scientific and philosophical thoughts as they are developed and practiced in Pakistan or in other words, bringing the Islamic and western incliners close to each other and also in outlining some practical methodological ways through which this process of integration can be put on track leading towards a forward looking and modern Pakistani society while retaining its core and basic fabric of faith and religion. The paper has three sections, the first section highlights the needs and reasons for synthesis in relation to various segments of our society and also point out the potential adverse consequences of not undertaking and building an integrative view. The second section suggests some ways, measures and methods of achieving the above mentioned thought of integration across the society and focuses on some of the collective and institutional level endeavors and commitments required to actualize this integration. The third section of this paper issues some warnings regarding the process of integration and its possible undesirable repercussions on the society, in light of some of the earlier such attempts. The research draws some practical steps which need to be undertaken in the Pakistani society for creating a synthesis between Faith and Reason.
Keywords: 330; philosophical thoughts